Experimental Study on Mold-Lay Filament instead of Wax in Investment Casting Process - Imam Kusyairi; Helmy Mukti Himawan; Moch. Agus Choiron; Yudy Surya Irawan; Rachmat Safari; Dagus Resmana Djuanda (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2020)
Metal casting with investment casting method is metal casting which has the ability to produce accurate parts and has a controlled fineness. Current technological developments are very influential in the development of investment casting. One of them has been found mold-lay filament as a substitute for wax, which is now wax is one of the main components in investment casting process. Mold-lay filament is printed using a 3D Printer machine. In this study, the wax in the investment casting process was replaced by a mold-lay filament with the specifications 0.75kg / 0.55 lb of 1.75mm MOLDLAY filament, prints at temperatures of 170-180° C. The result show that mold-lay flutes are also able to come out well from slurry molds, but require more time than wax, this is because one of the plastic mold-lay compositions, which takes a long time for the moldlay fillment to come out of the mold. Further research suggestions are needed further testing in terms of roughness of the product with moldlay filament and compared with wax. This will also see if there are any remaining moldlay filaments from the mold.